(untitled) (Jurnal Adabiya, 2025)
Indonesia is one of the countries with the highest disaster vulnerability in the world, making disaster literacy a fundamental necessity for communities, especially those living in disaster-prone regions such as West Sumatra. In this context, Minangkabau local wisdom holds significant potential to strengthen disaster education through the cultural values embedded in community life. This study aims to analyze the practice of disaster literacy at the Bukittinggi Public Library and to identify how local values such as ‘Alam Takambang Jadi Guru’ (Nature as a Teacher), gotong royong (mutual cooperation), and ‘Bajanjang Naiak, Batanggo Turun (hierarchical but participatory cooperation) are integrated into community literacy activities. Using a qualitative descriptive approach with a case study method, data were collected through in-depth interviews, participatory observation, and institutional document analysis. The results reveal that the Bukittinggi Public Library actively fosters disaster awareness through culturally based literacy activities such as storytelling with disaster themes, collaborative disaster mitigation programs with institutional partners, and post-disaster trauma healing sessions. Minangkabau cultural values serve as a foundation for social learning that nurtures empathy, solidarity, and ecological awareness among the community. These practices expand the library’s role beyond an information center into a cultural space that bridges modern scientific knowledge with local wisdom. The study highlights that disaster literacy grounded in local culture enhances community resilience, enriches public literacy practices, and provides new directions for developing public libraries as agents of socio-cultural transformation rooted in humanistic and sustainable values